Trigeminal neuropathic pain is alleviated by inhibition of Cav3.3 T-type calcium channels in mice. Issue 1 (1st January 2021) - Montera, Marena; Goins, Aleyah; Cmarko, Leos; Weiss, Norbert; Westlund, Karin N.; Alles, Sascha R. A.
ABSTRACT: In this brief report, we demonstrate that the Cav 3.3 T-type voltage-gated calcium channel subtype is involved in our FRICT-ION model of chronic trigeminal neuropathic pain. We first showed that the Cacna1i gene encoding Cav 3.3 is significantly upregulated in whole trigeminal ganglia of FRICT-ION mice compared to controls at week 10 post-injury. We confirmed protein upregulation of Cav 3.3 compared to controls using Western blot analysis of whole trigeminal ganglia tissues. Finally, we demonstrated that intraperitoneal injection of a selective TAT-based Cav 3.3 blocking peptide in FRICT-ION mice significantly reduces Cav 3.3 protein expression at the peak anti-allodynic effect (4 hrs post-injection) of the attenuated neuropathic pain behavior. We also suggest that blockade of Cav 3.3 may be more effective in attenuating trigeminal neuropathic pain in female than male FRICT-ION mice. Therefore, blocking or attenuating Cav 3.3 function may be an effective strategy for the treatment of trigeminal neuropathic pain.